2023
DOI: 10.1177/09603271231188492
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine ameliorates dasatinib-induced liver injury via decrease in hepatic lymphocytes infiltration

Khalid Alhazzani,
Salah Q Alrewily,
Khaldoon Aljerian
et al.

Abstract: Dasatinib is an effective treatment for chronic myeloid leukemia. However, cases of idiosyncratic hepatotoxicity were reported. This study was conducted to investigate the chemopreventive effects of hydroxychloroquine against dasatinib-induced hepatotoxicity. Balb/c mice were randomly assigned into four groups; vehicle control (5% DMSO, i.p., n = 6), dasatinib (50 mg/kg; i.p., n = 6), hydroxychloroquine (10 mg/kg, i.p., n = 6), and hydroxychloroquine + dasatinib (10 mg/kg + 50 mg/kg; i.p., n = 6). Treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…Research indicates that IL-6 may substantially impact B cell hyperactivity and could even directly impact tissue harm [23]. However, results show that HCQ was able to ameliorate Aspergillosis-induced hepatoxicity through concomitant reduction of IL-6 levels and decreased polymorphonuclear infiltrates [24]. Although zinc supplement has not been shown to result in higher expression of , the results from this study revealed higher expression of IL-10 when HCQ and zinc are simultaneously administered to experimental models.…”
Section: Discussioncontrasting
confidence: 56%
“…Research indicates that IL-6 may substantially impact B cell hyperactivity and could even directly impact tissue harm [23]. However, results show that HCQ was able to ameliorate Aspergillosis-induced hepatoxicity through concomitant reduction of IL-6 levels and decreased polymorphonuclear infiltrates [24]. Although zinc supplement has not been shown to result in higher expression of , the results from this study revealed higher expression of IL-10 when HCQ and zinc are simultaneously administered to experimental models.…”
Section: Discussioncontrasting
confidence: 56%
“…Research indicates that IL-6 may substantially impact B cell hyperactivity and directly impact tissue harm (26). However, other research showed that HCQ was able to ameliorate aspergillosis-induced hepatoxicity through concomitant reduction of IL-6 levels and decreased polymorphonuclear infiltrates (27). Although zinc supplements have not been shown to result in higher expression of IL-10 (28), the results from our study revealed higher expression of IL-10 when HCQ and zinc were simultaneously administered to the experimental rats.…”
Section: Discussionmentioning
confidence: 99%